Odziv potencialno prizadetih prebivalcev na nadaljnje širjenje ugrezninskega območja velenjskega premogovnika - Špeh, Natalija (Geografski vestnik, 2000)
Through a research quastionnaire, we determined the response of potentially affected population to the further spread of lignite coal mine in the western part of the Šalek Valley, where there are still intact exploitable reserves below the surface. We noted that the answers of urban and rural population were very similar.
Keywords: Šalek Valley; Šaleška dolina; premogovništvo; natural environment; okolje; degradacija; razvojna strategija; sonaravni razvoj; varstvo okolja; environmental protection; prebivalstvo